Salivary proteomic analysis in patients with type 2 diabetes mellitus and periodontitis - Furukawa, Monique Vieira; Oliveira, Marissol Fernandes; da Silva, Rodrigo Augusto; Máximo, Priscila Macedo; Dionizio, Aline; Ventura, Talita Mendes Oliveira; Cortelli, Sheila Cavalca; Corelli, José Roberto; Buzalaf, Marília Afonso Rabelo; Rovai, Emanuel Silva [UNESP] (Springer Nature, 2025)
Objective: This study aimed to compare the salivary protein profile in individuals with Type 2 Diabetes Mellitus (DM2) and periodontitis and their respective controls. Methods: Eighty participants were included in the study. The four groups were formed by individuals with DM2 and periodontitis (DM2 + P, n = 20), DM2 without periodontitis (DM2, n = 20), periodontitis without DM2 (P, n = 20) and individuals without periodontitis and without DM2 (H, n = 20). Periodontal clinical examinations were performed and unstimulated saliva was collected. Proteomic analysis was performed by shotgun mass spectrometry. The results were obtained by searching the Homo sapiens database of the UniProt catalog. Results: A total of 220 proteins were identified in saliva samples. In the comparison between DM2 + P and DM2 groups, 27 proteins were up-regulated [e.g. S100-A8 was 6 times up-regulated (humoral immune response pathway)]. The DM2 + P and P groups had 26 up-regulated proteins [e.g. Immunoglobulin lambda constant 7 more than 2 times up-regulated (complement activation pathway)]. The non-DM2 groups (P and H) presented 22 up-regulated proteins [e.g. Glyceraldehyde-3-phosphate dehydrogenase more than 2 times up-regulated (Peptidyl-cysteine S-nitrosylation pathway)]. The groups without periodontitis (DM2 and H) showed 23 were up-regulated proteins [e.g. Hemoglobin subunit alpha that was more than 10 times up-regulated (cellular oxidant detoxification pathway)]. Conclusion: The presence of DM2 and periodontitis significantly impacts the salivary proteome. Our proteomic analysis demonstrated that changes in the S100 family proteins (S100A8 and S100 A9) are highly related to the presence of DM2 and periodontitis. Clinical relevance: Diabetes Mellitus (DM) and periodontitis are highly prevalent chronic diseases that present a wide variety of signs and symptoms. They present a bidirectional relationship, where patients with DM have a higher prevalence and severity of periodontitis, and patients with periodontitis have a higher prevalence of DM, worse glycemic control, and more diabetic complications. Diagnosing periodontitis requires specific clinical examinations, which require a highly trained operator. In this study, we used high throughput proteomics in order to evaluate non-invasive biomarkers for periodontitis in type 2 DM subjects. The results can contribute to earlier, more accurate, and less costly diagnosis of periodontitis in diabetic subjects, enabling better diabetes control.
Keywords: Diabetes Mellitus; Periodontitis; Proteomics; Saliva